PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN PEGAWAI DI KANTOR PERTANAHAN KABUPATEN TEMANGGUNG - Kristina, Febe; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Humans are important assets that became a major concern in an organization, because humans are the planners, perpetrators and the deciding goal of the organization. Discipline is an important requirement in order to create the climate and atmosphere of the work for the sake of achievement of the objectives of the organization. Discipline work not optimal underlying this research that had done. Discipline was influenced by the style of leadership that gives direction to employees working based on the objectives of the Organization and the motivation that drove employees improve work discipline. This study uses quantitative analysis approach. The samples used in this study of 40 respondents who are employees of the Office of the Land district of Temanggung. Data analysis using simple linear regression analysis, multiple linear regression, f test, determination of the coefficient, t test with the help of program SPSS. The result showed that the influence of leadership style of the discipline of 27,6%, while the influence of motivation against the discipline of 23,1%, and discipline influenced the style of leadership and motivation at the same time of 31.5%. The results showed that there is a positive relationship between leadership style and motivation of discipline.